Online Teaching and Learning in Higher Education during COVID- 19: International Perspectives and Experiences: edited By Roy Chan, Krishna Bista, Ryan Allen, Routledge, 2022, 266 pp., ISBN 978-0-367-64715-5 - Ahmad, Pahrozi; Alqarni Akis, Muhammad Isnur (SALEE: Study of Applied Linguistics and English Education, 2023)
Successfully forced the global shutdown of several activities, including educational activities; the covid-19 pandemic has resulted in tremendous crisis-response migration of universities with online learning serving as the educational platform. In response to this phenomenon, this paper provides a wide range of ideas and perspectives on online teaching during the pandemic of covid-19. This paper also contributes to the existing research on online learning studies, especially in distance education.